Proposal and phylogenetic relationships of Lapsamita, a new genus of lapsiines, and description of a new species (araneae, salticidae). - Gustavo R S Ruiz (Public Library of Science (PLoS), 2013)
Lapsamita maddisoni gen. et sp. nov. is described from Bahia, Brazil. The presence of palpal claws in females, long ventral spines on front tibiae and metatarsi and long retrolateral tibial apophyses in male palps suggested that the species was closely related to or even nested within Soesiladeepakius Makhan, 2007. To evaluate its phylogenetic position, a cladistic analysis was carried out using a data matrix comprising 24 morphological characters, scored for 13 taxa. The analysis showed L. maddisoni as the sister group of Soesiladeepakius, supporting the proposal of the new genus. Character evolution is discussed and compared to a previous study on the group.